2021
DOI: 10.1021/acsanm.1c02487
|View full text |Cite
|
Sign up to set email alerts
|

Zr-Doped NiO Nanoparticles for Low-Temperature Methane Combustion

Abstract: The development of efficient and stable non-noble metalbased catalysts for low-temperature methane combustion is extremely important and still a profound challenge. Herein, high-performance Ni 1−x Zr x O 2−δ solid solution nanocatalysts were prepared through a homogeneous co-precipitation strategy, where the hydrolysis of CO 3 2− was controlled to facilitate the dispersion and interaction of Ni and Zr components. The structural and surface properties of nanocatalysts were facilely tuned by modulating the Zr do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 62 publications
1
16
0
Order By: Relevance
“…The authors did not mention which mechanism the CMC on Ni 0.89 Zr 0.11 O 2-δ conforms to, but according to the lattice oxygen and oxygen vacancies involved in the reaction, it is judged that the reaction conforms to the MvK mechanism. Meanwhile, in the stream tests, the steady conversion of CH 4 could be well maintained regardless of the presence of H 2 O due on the doping of Zr ( Wang et al, 2021 ).…”
Section: Transition Metal Oxides For Catalytic Ch 4 ...mentioning
confidence: 96%
See 2 more Smart Citations
“…The authors did not mention which mechanism the CMC on Ni 0.89 Zr 0.11 O 2-δ conforms to, but according to the lattice oxygen and oxygen vacancies involved in the reaction, it is judged that the reaction conforms to the MvK mechanism. Meanwhile, in the stream tests, the steady conversion of CH 4 could be well maintained regardless of the presence of H 2 O due on the doping of Zr ( Wang et al, 2021 ).…”
Section: Transition Metal Oxides For Catalytic Ch 4 ...mentioning
confidence: 96%
“…NiO, NaCl-type cubic spar structure, is a typical P-type semiconductor with the intrinsic defects at the Ni 2+ metal sites, which give rise to positive holes (p + ) to generate Ni 3+ (Ni 2+ + p + →Ni 3+ ) or O − species (O 2− + p + →O − ). NiO is extensively used in the field of catalysis, chemical sensors, battery electrodes, and magnetic and electronic devices due to excellent properties such as catalytic activity, thermo-sensitivity, and super-paramagnetic property ( Wang et al, 2021 ). Especially, in the field of catalysis, NiO-based catalysts attract a lot of attention due to the surface electrophilic O 2− species being effective for the activation of C–H bonds.…”
Section: Transition Metal Oxides For Catalytic Ch 4 ...mentioning
confidence: 99%
See 1 more Smart Citation
“…They further discovered that Pd 4+ -Pd 2+ redox pairs could serve as active components for methane combustion. , Moreover, it was found that dopants in groups IV and V enhanced the CeO 2 catalyst for methane combustion via tuning its reducibility, while the dopants in groups X–XII became extra reduction centers themselves . Wang et al discovered that the NiO nanoparticles doped by Zr contained more Ni 2+ species, which were active sites for methane combustion. Toscani et al discovered that the introduction of Sc into CeO 2 -ZrO 2 catalysts demonstrated a significant increase in catalytic activity, which was due to the lattice defects and oxygen mobility.…”
Section: Catalystsmentioning
confidence: 99%
“…Besides, a slight absorption band was observed at 420 nm, indicative of Ni 3+ species. 44,45 The XPS measurements were employed to investigate the elemental properties of Ni, O, and Mn atoms in the un-doped and 0.5% Mn-doped NiO x lms. It is well known that hole transport ability of nonstoichiometric NiO x comes from the existence of Ni 3+ (Ni 2 O 3 species) in the crystalline structure.…”
Section: Characterization Of the Un-doped And Mn-doped Nio Xmentioning
confidence: 99%